(untitled) (Bangladesh Medical Journal, 2023)
Limited access to safe abortion is a leading cause of maternal mortality and morbidity in the developing world, overwhelming hospitals with a large number of women seeking treatment for complications of unsafe abortion. In many cases, more than half of all gynecological admissions are due to incomplete or septic abortions. The primary aims were to assess the efficacy and cost-effectiveness of the manual vacuum aspiration (MVA) procedure for managing incomplete abortion, considering completeness, procedure, duration, and hemorrhage. Additionally, safety aspects, such as complications (hemorrhage, perforation, and cervical injury), pain relief, patient satisfaction, and factors like reduced hospital stays and waiting times, were evaluated. This descriptive cross-sectional study was conducted at Dhaka Medical College and Hospital, focusing on women with incomplete abortions up to 12 weeks of gestation. It took place over six months from July to December 2013, with a purposive sample of 100 cases selected based on specific criteria to represent the study’s objectives. Statistical analysis was done by using SPSS (version 16.0, SPSS Inc., Chicago, Illinois, USA). Out of 100 respondents, more than two-third of the patients (68%) were in 21-30 years age group. Half of the patients (50%) came from lower middle class family and most of them were housewives (80%). Majority (58%) of the patients had average gestational age 6-10 weeks. More than two-third (70%) of the patients had incomplete abortion, with 47% having attempted to terminate pregnancy. Abdominal pain was reported among 64% of patients, and the average bleeding period was 5-7 days for 62% of them. More than two-third (68%) of patients had no palpable uterus, and active bleeding was also found among two-third 66.0% of cases. Nearly one-third of the patients (32%) received injectable oxytocin and 13% received blood transfusion. Method of para-cervical block was applied for pain management in all patients (100%), while pethidine was used in only 3% of cases. Almost all of the patients 97%) were given sedatives (diazepam) and oral non-steroidal anti-inflammatory drugs (NSAIDs). Duration for the procedure was 10-15 minutes for 46% of patients, and excessive hemorrhage was found in 2% of cases. The average hospital stay ranged from 2-11 hours. Treatment cost in the majority of cases was only 75-150 Bangladeshi taka (BDT), which was statistically significant. The MVA with paracervical block was found to be efficient for treatment of incomplete abortions during the first trimester of pregnancy, with few complications. MVA procedure had less blood loss, less time consuming, safe and effective with shorter hospital stay. Bangladesh Med J. 2022 May; 51(2): 21-29